2006
DOI: 10.1002/kpm.257
|View full text |Cite
|
Sign up to set email alerts
|

An empirical examination of performance measurement for managing continuous innovation in logistics

Abstract: Performance measurement within organisations identifies areas of a business that need attention and improvement. The measurement and control of logistics performance requires the selection of critical performance measures and the development of information systems to gather required data, report on variance analysis and recommend corrective action. The logistics function is increasing in its strategic importance as more and more firms in developed economies such as Singapore and Australia are forced to compete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 24 publications
1
30
0
1
Order By: Relevance
“…Performance measurements are useful diagnostic tools for better decision-making and a key requirement of successful continuous innovation (Soosay & Chapman, 2006). Researchers have proposed various frameworks for supply chain performance, in order to qualify the efficiency and the effectiveness of the supply chain, where different dimensions of supply chain performance are considered (Lin, Huang & Li, 2002;Lin & Li, 2010;Gunasekaran et al, 2004;Sillanpää & Kess, 2011).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Performance measurements are useful diagnostic tools for better decision-making and a key requirement of successful continuous innovation (Soosay & Chapman, 2006). Researchers have proposed various frameworks for supply chain performance, in order to qualify the efficiency and the effectiveness of the supply chain, where different dimensions of supply chain performance are considered (Lin, Huang & Li, 2002;Lin & Li, 2010;Gunasekaran et al, 2004;Sillanpää & Kess, 2011).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The studies on the CI and its application in various sectors, scales, and types of industry, such as manufacture industry [5], [6], services industry [7], [8], social sector [9], high-tech industrial cluster [10], Small and Medium-sized enterprises or clusters [11], [13], mature and slow moving industry [14], and rapidly changing industry [15], indicated that there are different definitions and concept of "continuous innovation". The connotation of the word "continuous" in several studies are sometimes linked to the extent to which the innovation change is made, such as continuous improvement [16].…”
Section: Introductionmentioning
confidence: 99%
“…Performance measures may also be classified according to their strategic or operational usage (e.g. Soosay and Chapman 2006). For instance, strategic performance measures would comprise key metrics for leadership, strategic planning, human resource management, customer satisfaction, and process quality.…”
Section: Strategies For Monitoring Supply Chain Performancementioning
confidence: 99%
“…In case any of the quadrants is empty after all parameters are entered, the area should be revised again to be sure it is either on purpose that there is no entrance or until the white spot area is filled. The division into strategic and operational performance measures has been researched in field studies (Soosay & Chapman, 2006). They show that there is a disproportionate focus on costs (42%) over non-cost measures such as quality (28%), time (19%), flexibility (10%), and innovativeness (1%).…”
Section: Hierarchies Of Performance Measuresmentioning
confidence: 99%